Telemedicine: a Primer - Waller, Morgan; Stotler, Chad (Current allergy and asthma reports, 2018)
Purpose of Review Due to rapid advancements in quality of real-time, interactive, audio-visual, and digital technologies as well as impressive gains in internet speed and capacity, medicine delivered over distance is happening faster than many healthcare providers and leaders can grasp. Recent Findings Depending on which market report you ascribe to, industry projections for the global compounded annual growth rate of telemedicine are between 13 and 27%, with valuation growing to over 20 billion US dollars in the next several years. The Mayo Clinic has reworked its entire telemedicine interest to a model with centralized operations, one virtual technology platform, standardized training, and connectedness for all of its locations. The National Quality Forum spent 2016 and 2017 formulating 70 some pages of recommendations for expanded measures to valuate telemedicine over the foreseeable future. There are so many patient experience studies indicating high satisfaction with telemedicine, that professionals in the industry accept it as fact. Telemedicine is leaving novel to the past. Summary This short, informative piece of writing includes expert opinion and research findings about what is telemedicine, why one should practice telemedicine, and how one should approach implementation; a primer from which to grow.